Cool thermodynamics : the engineering and physics of predictive, diagnostic and optimization methods for cooling systems - Gordon, Jeffrey M. (Cambridge International Science Pub., 2001)
This book is geared toward those interested in the engineering and physics of air-conditioning and refrigeration devices (chillers). Analytic thermodynamic models are developed for a wide variety of cooling systems and a broad range of operating conditions. These models are easily implemented in the field or laboratory.